A rare case of ruptured gravid horn of a bicornuate uterus - Borthakur, Pratyusha; Munisamaih, Munikrisha (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
The incidence of the uterine malformations is estimated to be 3% to 5% in the general population. Bicornuate uterus (BU) is a rare uterine anomaly result from incomplete fusion of the two Müllerian ducts during embryogenesis. Bicornuate uterus very rarely can lead to rupture of the uterus during the early pregnancy with high mortality and morbidity rates. In this case, rupture was diagnosed at an earlier gestational age, where the patient was also stable. There was a favourable outcome with timely intervention.